Training of Prisoners in the Making of Accessories at Keerom-Papua Women's Prison, Class III A - Janni Beatrix Mandowally; Nurliya Apriyana; Lingga Yuliana (CV. Aksara Global Akademia, 2024)
The purpose of this course is to give participants the opportunity to support their families financially after their release from jail and to enhance the abilities and skills of women incarcerated or imprisoned. Therefore, the training's benefit is to boost the participants' self-confidence so they can engage the community after being released and realize their potential as accessory artisans. Insight and advantages are gained from the instruction, both for the individual and for other female inmates. Because they possess skills that they can utilize after they are released from prison, this instills confidence in the convicts. With the use of this provision, female inmates aspire to benefit themselves, their families, and the nation by giving similar training to underserved local populations, which will lead to the creation of jobs and tax revenue for the state.